LIP REJUVENATION WITH HYALURONIC ACID: CASE REPORT - Hennaly Silva Dantas, Ashley; Vanessa Machado Bezerra, Rosane; Toshiaki Nojima, Carlos; Matheus de Andrade Lira, Kainã; Dias Gomes da Silva, Gustavo; Galindo de Oliveira, Janaina; Gomes Moreira, Andréia (Health and Society, 2022)
In Dentistry, the search for positive changes in the aesthetics of the smile has been increasing and with that the objectives have become broader, not being restricted only to the teeth, but also treating both the functional and aesthetic parts of the face, known as Orofacial Harmonization. With aging, tissue loss and aggravation resulting from the effects of gravity, it is observed atrophy in the region of the lips with the erasure of the philtrum region, the inversion of the vermilion of the lips and the appearance of perioral wrinkles. Injectable fillers can be used to improve and volumize lip proportions, as well as favoring the perioral region, with Hyaluronic Acid (HA) being the most used as a filling material. The search for an immediate result has made HA fillers increasingly popular for harmonizing lips, due to their cost-effectiveness and minimally invasive nature. The professional is responsible for performing therapeutic treatments in order to improve the quality of life of their patients, including the use of HA for functional and/or aesthetic therapeutic purposes.